Dehydrogenation kinetics of MgH2-based hydrogen storage tank at different operating temperatures and mass flow rates. (5th February 2022) - Dansirima, Palmarin; Pangon, Autchara; Utke, Oliver; Utke, Rapee
Abstract: The most efficient electrical production from fuel cells integrated with hydride-based hydrogen storage tanks is obtained from suitable dehydrogenation kinetics, facilitating constant flow rate of hydrogen supply for a long period of time. Dehydrogenation kinetics of hydride-based tanks depends strongly on operating temperatures and system pressures, relating to hydrogen mass flow rate (H2 -FR) released from the tank. Since a cylindrical tank (96.2 mL) mounted with central heat exchanger containing TiF4 -MWCNT-MgH2 (∼45 g) shows excellent de/rehydrogenation and reversibility (5.4 wt % H2 upon 20 cycles), the effects of different operating conditions (T = 300–340 °C and H2 -FR = 0.6–1.0 standard L/min) on kinetic properties of this MgH2 -based tank are of significant interest. Kinetic properties either rapid or steady-state desorption can be optimized by tuning the operating temperature and H2 -FR simultaneously. Moreover, the performances in the axial and radial directions of the tank as well as kinetic behaviors and rate-limiting step during dehydrogenation at different temperatures and H2 -FR of MgH2 -based tank are investigated. Highlights: Effects of temperature (T) and H2 release rate (H2 -FR) on desorption of MgH2 -based tank. Optimized T and H2 -FR for steady-state H2 desorption favoring integration with fuel cells. Best desorption kinetics obtained from not only at elevated T but also fast H2 -FR. Investigation of desorption kinetics in the axial and radial directions of the tank. Studies of kinetic behaviors and rate-limiting step of MgH2 -based laboratory and tank scales.